THE GENETIC DIVERSITY AND ANCESTRY OF A SMALL SAMPLE FROM GREATER KURDISTAN: INSIGHTS FROM DNA SEQUENCING RESULTS - AKBAR, SIRWAN AZIZ. (Journal of Duhok University, 2023)
In this research, the DNA sequencing method is used to analyse the genetic diversity and ancestry of a small group of people from greater Kurdistan. The ancestry report data indicates the anthropological roots of the individual. It's interesting to note the distribution of the DNA sequencing results of the Kurdish specimens. The results showed that the Kurdish-origin volunteers from Greater Kurdistan had a high degree of genetic similarity, indicating a common genetic ancestry. The sequencing showed that all Kurds from Greater Kurdistan share approximately similar origins. All regions and countries with ancestry in these results were either Kurdish lands or settled by Kurds. In addition, the data revealed that volunteers from other countries, compared to Kurds, displayed a lower level of genetic similarity, indicating a more diverse genetic ancestry. i.e., the significance of the distinctions between Kurds from all regions of Greater Kurdistan and other ethnicities from Turkey, Iraq, Iran, and Israel, as well as ethnicities from the remaining countries (the United Kingdom and Spain), confirms the accuracy of the findings. The results of this study are important for understanding the genetic diversity and ancestry of the Kurdish population. It provides a detailed picture of the genetic makeup of the Kurds, which can be used to understand better the history and culture of the Kurdish people. However, it is important to emphasise that these estimates are based on the individuals who were sampled for the study and may not represent the genetic diversity of the entire population of Greater Kurdistan. It's also important to note that various factors such as migration, historical events, and genetic drift can influence genetic ancestry, which is a complex topic. The fact that the specimen's DNA is predominantly linked to Iraq, Iran, Turkey, Syria, Armenia, Pakistan, and Lebanon suggests that the region may have played a vital role in the ancestry of the individual to which the specimen belonged, or historical genetic ties between the Kurd regions and their countries that are related; or Kurds have with time become multiethnic due to admixture with other groups, and this is due to more recent migrations or genetic exchanges (intermarriages) between those regions and Kurds. Additionally, ten major haplogroups (Hg) of the Y-chromosome Kurdish gene pool were determined, which indicates a diverse genetic background. Among these haplogroups, J, R (R1b), G, and E were considered the most common. However, the results of the present study are not totally significant and do not totally represent all Kurds; because of the limited sample size, they are considered a beginning for further research.